SWAT-DayCent coupler: An integration tool for simultaneous hydro-biogeochemical modeling using SWAT and DayCent. (December 2016) - Wu, Yiping; Liu, Shuguang; Qiu, Linjing; Sun, Yuzhu
Abstract: Process-based numerical models in environmental science can help understand and quantify terrestrial material cycles in nature. However, the existing models usually focus on the cycles of one or more elements (e.g., water, carbon, or nitrogen). For example, hydrological models such as Soil and Water Assessment Tool (SWAT) focus on the water cycle and nutrient loadings at watershed scale, whereas biogeochemical models such as DayCent (i.e., daily CENTURY) emphasize carbon/nitrogen storage and fluxes of ecosystems at landscape scale. Therefore, using either one of the two categories of models is not enough for understanding/solving the current complex environmental issues that involve multiple aspects. Although use of both models (SWAT and DayCent) could be an expedient way toward treating the problem, creating separate model projects for a single area could be challenging and time consuming, and integration/analyses of model results have some limitations due to the non-uniformity of input spatial data between models. To overcome this issue, we developed an integrated model implementation coupler that aims to drive SWAT and DayCent—the two representative models in hydrology and biogeochemistry, respectively—just using a user's SWAT project without the need of any extra efforts such as developing a framework or preparing input data for DayCent modeling. This software is easy to use and would be promising for conducting comprehensive environmental impact assessment involving hydrological and biogeochemical cycles at watershed scale. Highlights: SWAT-DayCent Coupler was developed to drive both SWAT and DayCent simultaneously. The software can help users integrate both model results on the HRU mapping units. The software can be readily used for an existing SWAT project without extra efforts.